New records of protostrongylid lungworms from wild ruminants in Bulgaria - M.S. Panayotova-Pencheva (Veterinární Medicína, 2006)
A necropsy of lungs from mouflons, chamois, red deerand fallow deer from Bulgariawas performed aiming at determining the species composition of protostrongylids. For the first time in the country Muellerius capillaris, Cystocaulus ocreatus, Neostrongylus linearis, Protostrongylus rufescens, P. hobmaieri are reported as part of the helminth fauna in the mouflon, M. capillaris, N. linearis and P. rupicaprae are reported from the chamois, and Varestrongylus sagittatus is reported from the red deer. This is the first record of P. hobmaieri, P. rupicaprae and V. sagittatus for the fauna of Bulgaria. Some morphological data of males and first stage larvae of P. hobmaieri on materials from the present study are presented